Examining the green factors affecting environmental performance in small and medium–sized enterprises: A mediating essence of green creativity - He, Di; Raza, Ali; Chen, Min; Xu, Yiwei; Morake, Otsile (Frontiers in Psychology, 2022)
Despite a large amount of literature on the management and sustainability of green enterprises, representatives’ contributions to environmental challenges have received scant attention. This study purposefully assesses how managers’ ecological expertise and ability to transform organizations’ leadership practices into more environmentally friendly ones, with the help of green creativity (GC) as a mediating factor. The study utilizes partial least square structural equation modeling to examine the perceptions of 400 respondents in various leadership roles in the small and medium businesses industry. The study’s findings point to the beneficial impacts of green knowledge (GK), green transformational leadership (GTL), and GC on environmental performance (EP). GC also appears to perform a meaningful mediating role in the links between GK and EP, GTL, and EP. The primary takeaway from recent research is that participants in the sector may be able to respond with green efforts that are specific to their businesses with the support of managers’ environmental concerns. There is a discussion on practice recommendations and future directions.